Antitumor treatment and cardiohemodynamics in patients with multiple myeloma depending on renal function - B. B. Samura; M. O. Panasenko (Zaporozhye State Medical University, 2020)
Purpose - to evaluate the relations of antitumor treatment and cardiohemodynamics in patients with multiple myeloma depending on renal function. Materials and methods. Fifty-one subjects with multiple myeloma were enrolled in the study. They were divided into groups depending on the glomerular filtration rate (GFR). First group involved 12 patients with GFR 30-59 ml/min/1,73 m2, second one - 14 patients with GFR 60-89 ml/min/1,73m2, third one - 25 patients with normal renal function. All patients underwent echocardiography before and after antitumor treatment. Results. In patients with GFR 30-59 ml/min/1.73 m2 ejection fraction was significantly lower in comparing with healthy persons (54.70 [51.20; 57.60] % versus 59.82 [57.81; 62.29] %; P = 0.012) mainly due to decreased end systolic volume (ESV) (55.90 [43.28; 59.39] ml versus 34,22 [31.72; 41.24] ml; P = 0.031). In this group ESV was significantly lower in comparing with patients with normal renal function. In patients with GFR 30-59 ml/min/1.73 m2 after antitumor treatment E (0.77 [0.59; 0.81] m/c, E/A (0.91 [0.86; 0.95] m/c were significantly lower in comparing with dates before treatment (P < 0.05). In patients with GFR ≥90 ml/min/1,73 m2 after antitumor treatment E/A (0.89 [0.72; 1.11] m/c were significantly lower in comparing with dates before treatment (P < 0.05). In patients with GFR 30-59 ml/min/1.73 m2 E (0.89 [0.75; 1.00] m/s versus 1.01 [1.02; 1.24]; P = 0.014), A (0.89 [0.77; 1.10] m/s versus 0.73 [0.56; 0.85] м/s; P = 0.020). E/A (0.98 [0.94;1.12] versus 1.16 [1.06; 1.25]; P = 0.011) were significantly lower in in comparing with control. Global circular systolic strain (-17.60 [-21.05; -15.18] versus -25.92 [-26.09; -19.15]; P = 0.012) and global circular systolic strain rate (-1.22 [-1.32; -1.20] versus -1.32 [-1.42; ‑1.25]; P = 0.022) was significantly lower in group of patients with GFR 30-59 ml/min/1.73 m2 in comparing with healthy persons. Conclusions. Our data suggest that the extent of renal function is directly associated with left ventricle diastolic and regional systolic parameters. Among patients with multiple myeloma and renal insufficiency systolic, diastolic, and regional systolic contractility were significantly worse in comparing with patients with normal renal function and healthy persons. Antitumor treatment of multiple myeloma has a negative effect on diastolic and regional systolic function. These dates may be used for the prognosis of cardiovascular events.